1982
DOI: 10.1099/0022-1317-62-2-297
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Neutralization-specific Antigen of a Calf Rotavirus

Abstract: SUMMARYMonospecific polyclonal antisera were raised in guinea-pigs against the calf rotavirus polypeptides VP 1, VP2, VP3* + 4*, VP4.2, VP6, VP7. I, VP7.2 and VP 10. All of the antisera gave a similar pattern of cytoplasmic immunofluorescence in rotavirus-infected cells, but spots of fluorescence of varying intensity with different sera were seen over the nucleus. Immune precipitation, using Staphylococcus aureus to collect immune complexes, showed that VP2 was precipitated by antiserum to VP2 (ct-VP2) and VP6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

1983
1983
1994
1994

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…It has previously been reported that simian rotavirus SA-11 can give one or two glycoprotein bands (Estes et al, 1981. Two glycoprotein bands of VP7 have also been reported for calf rotavirus (Killen & Dimmock, 1982;McCrae & McCorquodale, 1982). The occurrence of two glycoprotein bands of VP7 within an unplaqued stock of human rotavirus could be due to a mixture of several different phenotypes as suggested by Estes et al (1982).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It has previously been reported that simian rotavirus SA-11 can give one or two glycoprotein bands (Estes et al, 1981. Two glycoprotein bands of VP7 have also been reported for calf rotavirus (Killen & Dimmock, 1982;McCrae & McCorquodale, 1982). The occurrence of two glycoprotein bands of VP7 within an unplaqued stock of human rotavirus could be due to a mixture of several different phenotypes as suggested by Estes et al (1982).…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, recognition that the non-enveloped rotaviruses encode for two glycoproteins, one structural and one non-structural, is of special interest (Ericson et al, 1983;. The structural glycoprotein of human rotavirus has only been subjected to some characterization (Rodger et al, 1977) whereas simian and bovine rotaviruses are well characterized (Ericson et al, 1983;Estes et al, 1982;Killen & Dimmock, 1982;Matsuno & Mukoyama, 1979). Available data indicate that the glycoprotein, which is the type-specific neutralization antigen (Bastardo et al, 1981 ;Killen & Dimmock, 1982), contains an N-linked oligosaccharide with a high-mannose oligosaccharide moiety .…”
Section: Introductionmentioning
confidence: 99%
“…The outer shell proteins are the most relevant for the serological distinction of BI~V (17,19,22,29,31). Of the three polypeptides identified in the outer shell of BRV 1005 that of molecular weight 36,000 and corresponding to VP 7 (23) is the major protein, followed by a polypeptide of molecular weight 60,000.…”
Section: Discussionmentioning
confidence: 99%
“…A similar polypeptide composition was reported for the outer shell of BI~V UK (34) and BRV NCDV (22). Some authors have described a further outer shell protein of BRV with molecular weight similar to that of VP 7 (6,19,21), whilst others have attributed this protein to the inner shell (23). Novo et al (28) and McCRAE and FAULKNER-VALLE (23) described a VP 4 protein as a prominent outer shell constituent.…”
Section: Discussionmentioning
confidence: 99%
“…The genomic dsRNA is enclosed within a doublelayered protein capsid formed by at least five structural polypeptides (Novo & Esparza, 1981;Ericson et al, 1982). Two proteins present on the outer capsid of rotaviruses, VP3 and VP7, elicit antibodies capable of neutralizing virus infectivity (Greenberg et al, 1983a, b;Killen & Dimmock, 1982;Matsuno & Inouye, 1983). Recently, Hoshino et al (1985) have demonstrated that both proteins are equally immunogenic.…”
Section: Introductionmentioning
confidence: 99%